Methodology of Reflection of Cash Flows of Capital Investments in Financial Statements According to International Standards: Metodologi Pencerminan Arus Kas Investasi Modal dalam Laporan Keuangan Menurut Standar Internasional - Mukhammadiev Zarrukh Umarovich (Universitas Muhammadiyah Sidoarjo, 2024)
In the article, the information covered in the cash flow statement, the actual state of the reflection of items related to capital investments in the form of this report was studied, and recommendations were developed for the reflection of information on capital investments in the statement of cash flows. Also, international experiences reveal the issues of covering long-term assets such as investment property and biological assets in the cash flow statement Highlights: Analyzed cash flow statements and capital investment reflections. Developed recommendations for reporting capital investments. Examined international practices on long-term asset reporting. Keywords: statement of cash flows, capital investments, capital investment accounting, investment property, biological assets, accounting, international standards of financial reporting